2014
DOI: 10.1186/s12955-014-0137-9
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in quality of life associated with biphasic insulin aspart 30 in type 2 diabetes patients in China: results from the A1chieve® observational study

Abstract: BackgroundBased on the 24-week, prospective, non-interventional, observational study, A1chieve®, we investigated how health-related quality of life (HRQoL) changed, and the predictors of such changes, in Chinese people with type 2 diabetes mellitus (T2DM) after starting with, or switching to, biphasic insulin aspart 30 (BIAsp 30).MethodsIn total, 8,578 people with T2DM starting treatment with, or switching to, BIAsp 30 were recruited from 130 urban hospitals in China. HRQoL was assessed at baseline and 24 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
7
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 30 publications
5
7
1
1
Order By: Relevance
“…Also, patients switched from human insulins to insulin analogues reported improvement in QoL [20]. Similar results were obtained in a Chinese observational study evaluating the effect of initiation of biphasic insulin aspart 30 in 6,612 insulin naïve patients, or switching to this insulin analogue in 1,966 already insulin-treated subjects [21]. In a Dutch prospective cohort study, initiation of insulin glargine in both insulin-naïve as well as in insulin-treated patients with type 2 diabetes, resulted in improvement in QoL [22].…”
Section: Discussionsupporting
confidence: 80%
“…Also, patients switched from human insulins to insulin analogues reported improvement in QoL [20]. Similar results were obtained in a Chinese observational study evaluating the effect of initiation of biphasic insulin aspart 30 in 6,612 insulin naïve patients, or switching to this insulin analogue in 1,966 already insulin-treated subjects [21]. In a Dutch prospective cohort study, initiation of insulin glargine in both insulin-naïve as well as in insulin-treated patients with type 2 diabetes, resulted in improvement in QoL [22].…”
Section: Discussionsupporting
confidence: 80%
“…In addition, positive changes were also evident in a three-week walking programme reported in the study of GoldhaberFiebert et al although insignificantly small. 48,49 The percentage decline in LDL-C (11.9%) observed in this study is greater than the value in the meta-analysis conducted by Kelly and Kelly which indicated a significant reduction by 5% for LDL-C. 50 The improvement in TC, T, HDL-C-C and LDL-C exhibits clear evidence of reduction in atherogenic traits of risk factors 51,52 and better quality of life [53][54][55] of the sample studied. Authors observed that there are variations in the findings associated with this study in literature which are attributed to intensity, duration and frequency of exercise trainings and sample sizes.…”
Section: Discussioncontrasting
confidence: 53%
“…26 In the present study, patients treated with BIAsp 30 plus metformin had significantly higher patient satisfaction scores than patients receiving BIAsp 30 alone. 26 In the present study, patients treated with BIAsp 30 plus metformin had significantly higher patient satisfaction scores than patients receiving BIAsp 30 alone.…”
Section: Safetysupporting
confidence: 44%
“…A large observational study in China found that premixed insulin improved quality of life for type 2 diabetes patients. 26 In the present study, patients treated with BIAsp 30 plus metformin had significantly higher patient satisfaction scores than patients receiving BIAsp 30 alone. Given that weight gain was lower in patients receiving BIAsp 30 plus metformin, it is possible that this contributed to the higher satisfaction level in that group.…”
Section: Safetysupporting
confidence: 44%